1981
DOI: 10.1111/j.1570-7458.1981.tb03103.x
|View full text |Cite
|
Sign up to set email alerts
|

COURTSHIP BEHAVIOUR OF NASONIA VITRIPENNIS: HEAD NODDING, MOUTH‐PART EXTRUSION AND PHEROMONE DISCHARGE BY ABDOMECTOMIZED MALES

Abstract: Courting males of the parasitic wasp Nasonia vitripennis appear to release a pheromone with the extrusion of mouth parts during so-called head-nodding behaviour. This pheromone provokes sexual receptivity in conspecific virgin Q $. Abdomectomized c~ c~ court readily but have lost the ability to induce receptivity. Head nodding, mouth-part extrusion, and presumably also pheromone discharge, are absent from their courtship behaviour. However, plugging the injury results in reappearance of these motor patterns, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…First, the abdomen dipping frequency showed similar change trends to the protein level of SCD5a either along with the aging process or between unmated and mated males. Considering abdomen dipping behavior should be highly associated with attracting pheromone synthesis and release (van den Assem et al, 1981), we considered that linoleic acid for attracting pheromone production may also originated from the head (Ruther et al, 2011; Steiner & Ruther, 2009). Second, qPCR results indicated a significantly higher level of EH1 in head than in abdomen, indicating that the third step for attracting pheromone synthesis, from 12,13‐epoxy‐octadec‐9Z‐enpic acid to (12R,13S)−12,13‐dihydroxy‐octadec‐9Z‐enoic acid (Figure 1) might mainly take place in head than in abdomen.…”
Section: Disscussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the abdomen dipping frequency showed similar change trends to the protein level of SCD5a either along with the aging process or between unmated and mated males. Considering abdomen dipping behavior should be highly associated with attracting pheromone synthesis and release (van den Assem et al, 1981), we considered that linoleic acid for attracting pheromone production may also originated from the head (Ruther et al, 2011; Steiner & Ruther, 2009). Second, qPCR results indicated a significantly higher level of EH1 in head than in abdomen, indicating that the third step for attracting pheromone synthesis, from 12,13‐epoxy‐octadec‐9Z‐enpic acid to (12R,13S)−12,13‐dihydroxy‐octadec‐9Z‐enoic acid (Figure 1) might mainly take place in head than in abdomen.…”
Section: Disscussionmentioning
confidence: 99%
“…For males, greater reproductive success results from mating with females (Steiner & Ruther, 2009; van den Assem et al, 1981), while for virgin females, their response to pheromones is dose‐dependent, preferring males with higher pheromone stocks (Blaul & Ruther, 2011; Ruther et al, 2009). Increased SCD5a protein level and abdomen dipping frequency from Day 1 to Day 3 suggested that aged males might release more attracting pheromone and possess a higher possibility of successful mating.…”
Section: Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After copulation, males perform post‐copulatory courtship including additional series of head‐nodding behavior. A detailed analysis of the courtship behavior in the four Nasonia species revealed some subtle species‐specific differences (van den Assem & Vernel, ; van den Assem et al., , ; van den Assem & Werren, ). Although not completely strict, the females’ choosiness has the potential of playing a major part in maintaining prezygotic reproductive isolation between sympatric Nasonia species.…”
Section: Introductionmentioning
confidence: 99%